Coal direct chemical looping process: 250 kW pilot-scale testing for power generation and carbon capture. (15th January 2021) - Zhang, Yitao; Wang, Dawei; Pottimurthy, Yaswanth; Kong, Fanhe; Hsieh, Tien-Lin; Sakadjian, Bartev; Chung, Cheng; Park, Cody; Xu, Dikai; Bao, Jinhua; Velazquez-Vargas, Luis; Guo, Mengqing; et al.
Highlights: Demonstrated coal combustion and carbon capture with chemical looping at pilot scale. Achieved 288-h continuous operation and >1000 h of cumulative testing. Achieved >96% coal conversion and >97% CO2 purity. Demonstrated <2% carbon carryover from the reducer to the combustor. Abstract: Chemical looping combustion (CLC) is an energy conversion technology that can produce concentrated CO2 stream without the need for a gas separation step, and thus, has the potential to drastically reduce the energy consumption and cost associated with CO2 capture in power generation. The coal-direct chemical looping (CDCL) process is a CLC technology that uses a moving bed reducer configuration that can directly consume coal as a feedstock without requiring an upstream gasification step. An integrated 250 kWth CDCL pilot unit using iron-based oxygen carriers was constructed and demonstrated for over 1000 h of testing. The principles for the CDCL pilot unit design and operation are summarized in this article. During the 288-hour continuous operation testing, the CDCL pilot unit achieved >96% coal conversion with a CO2 purity of >97%. Low carbon carryover into the combustor, i.e. <2%, was also confirmed during the test, which shows the capability of the moving bed reactor to retain and convert coal using the oxygen available on the iron-based oxygen carrier. The results from the pilot unit testing confirms the CDCL concept as a promising coal combustion technology for heat and power generation with CO2 capture.